IMPLIKASI MEDIA SOSIAL DALAM PERGESERAN GAYA HIDUP PEMUDA DI DESA KANEYAN KECAMATAN TARERAN - Fabio Gigir; Abdul Rasyid Umaternate; Yoseph Santie (Labor Program Studi Pendidikan Sosiologi, 2021)
The purpose of the study was to describe the implications of social media in youth lifestyle shifts (Study of Social Change in Kaneyan Village, Tareran District, South Minahasa Regency). The method used in this study is a qualitative descriptive method, using an analytical approach that aims to describe and accurately describe systematically and actually the implications of social media in lifestyle shifts in youth by using observation, documentation, and interview techniques as data collection techniques. The results show that the implications of social media in the shift in youth lifestyles greatly affect the lifestyle habits of youth. The factors that cause them to be affected are lifestyle industry factors, lifestyle advertising, public relations and lifestyle journalists, and hedonic lifestyles. From the results of the research that has been stated, it is hoped that it can be useful for lecturers, students, prospective students, in order to develop education, especially at Manado State University.